Síntese e avaliação biológica de novos híbridos moleculares derivados de 5’-arilcalcogenil-3-amino-timidina e 2,4,6-tricloro- 1,3,5-triazina - Rocha, Nayra Salazar (2023)
The search for synthetic strategies that allow the efficient hybridization of biologically active molecules has gained attention among researchers, since they allow access to wide multiactive pharmacological varieties. In this sense, a series of molecules were synthesized in this work using 2,4,6-trichloro-1,3,5-triazine (cyanuric chloride), due to its properties that allow its functionalization with a versatility of molecules in a regiochemical way. Unpublished compounds derived from cyanuric chloride were obtained and characterized with different 5'arylcalcogenyl-3-amino-thymidine derivatives of zidovudine. Based on in silico tests, compounds 5a-5i showed favorable molecular docking results for interaction with the main protease active site of SARS-CoV-2, indicating promising antiviral activity. In silico and in vitro assays of the compounds obtained were also carried out to evaluate the antitumor activity. The in silico studies were carried out for the αβ-tubulin protein (dimer) and the in vitro studies against two cancer cell lines H-29 and NCI/ADR-RES, which showed effective inhibitory activity at low concentrations, highlighting the compound 5b. Studies of antioxidant activity were also performed by TBARS assay in which compound 5b at concentrations of 10 μM, 20 μM C and 200 μM significantly prevented lipid peroxidation induced by 100 μM FeSO4 in phosphatidylcholine samples.